227k views
3 votes
Using the method of substitution solve the problem need help completely loss if you can do it quickly it would help

Using the method of substitution solve the problem need help completely loss if you-example-1
User Stenerson
by
6.2k points

1 Answer

6 votes
Equation 1) y=x+3
Equation 2) y=2x+5

Rearrange both equations so that (x) and (y) are on the same side.

1) -x+y=3
2) -2x+y=5

Subtract equations with each other.

x=-2

Plug in -2 for (x) in equation 1.

y=(-2)+3

Simplify.

y=1

(-2, 1)

~Hope I helped!~
User Xatenev
by
5.9k points